2007
DOI: 10.1111/j.1365-3156.2007.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of sulfadoxine–pyrimethamine and the prevalence of molecular markers of resistance in under 5‐year olds in Brazzaville, Congo

Abstract: Summaryobjective To test the efficacy of sulfadoxine-pyremethamine (SP) monotherapy and establish the prevalence of mutations in dhfr and dhps in Brazzaville, Congo.method We recruited 97 patients aged 6-59 months with uncomplicated malaria who attended Tenrikyo public health centre. Eighty-three were followed until day 28. SP efficacy was determined by the WHO 28-day test and analysis of mutations in the Plasmodium falciparum dihydrofolate reductase (pfdhfr) and dihydropteroate synthase (pfdhps) genes. Mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…In the period 1992 to 2005, before adoption of ACTs, six efficacy in vivo studies had been conducted, of which one was based on the 1973 WHO protocol for asymptomatic children to assess chloroquine efficacy [20], one on 14-day follow-up WHO protocol to assess chloroquine and sulfadoxine-pyrimethamine (SP) [22], and four on the current 28-day follow-up WHO protocol to evaluate therapeutic efficacy of chloroquine [24], SP [25], ASAQ, AL and AS + SP [26], AL and then ASAQ [28, 30]. The study based on the 1973 WHO protocol was conducted in 1993 in three southern regions of the country (Niari, Kouilou and Pool which included Brazzaville) and the authors reported that 7 days after the standard three-day treatment with chloroquine at 25 mg/kg, 20–60% of cases were still found to carry malaria parasites [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the period 1992 to 2005, before adoption of ACTs, six efficacy in vivo studies had been conducted, of which one was based on the 1973 WHO protocol for asymptomatic children to assess chloroquine efficacy [20], one on 14-day follow-up WHO protocol to assess chloroquine and sulfadoxine-pyrimethamine (SP) [22], and four on the current 28-day follow-up WHO protocol to evaluate therapeutic efficacy of chloroquine [24], SP [25], ASAQ, AL and AS + SP [26], AL and then ASAQ [28, 30]. The study based on the 1973 WHO protocol was conducted in 1993 in three southern regions of the country (Niari, Kouilou and Pool which included Brazzaville) and the authors reported that 7 days after the standard three-day treatment with chloroquine at 25 mg/kg, 20–60% of cases were still found to carry malaria parasites [20].…”
Section: Resultsmentioning
confidence: 99%
“…SP efficacy was further assessed in the second phase of this study and the cure rate of 100% was recorded [22]. However, studies carried out using the 28-day follow-up WHO protocol showed high level of treatment failure for chloroquine (95.7%) [24] and SP (31.2%) [25], while AL and ASAQ were found to be highly effective to treat uncomplicated malaria with the reported 28-day PCR-corrected cure rates of 96.9 [30] and 100% [26] for AL, and 94.4% [28] and 98.5% [26] for ASAQ. AS + SP, with the 28-day PCR-corrected cure rate of 90% was also effective but less than AL and ASAQ [26].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the mode of action of this extract is different from that of chloroquine. This is an important finding in the context of malaria endemic regions where resistance to chloroquine is high and traditional medicine is highly practiced as it is the case in Congo-Brazzaville (Ndounga et al, 2007;Mbatchi et al, 2006). However, as organic extracts are not used by traditional healers to treat malaria, further in vitro antiplasmodial studies of drug combinations should be carried out using chloroquine or an artemisinin derivative and active compounds or fractions resulting from the active extract.…”
Section: Discussionmentioning
confidence: 95%
“…The effectiveness of IPTp-SP has not been evaluated so far and no published data on molecular markers of SP resistance among P. falciparum isolates from pregnant women is available. Previous studies conducted before the change of national guidelines for the treatment of uncomplicated malaria (in 2006) in Makélékélé district in the Southern part of Brazzaville reported approximately 10-47% in vivo resistance to SP in children (Ndounga et al, 2007a;Nsimba et al, 2004) and high prevalence rates of dhfr and dhps mutant genotypes (Ndounga et al, 2007b;Nsimba et al, 2005).…”
Section: Introductionmentioning
confidence: 98%